International atmosphere impact on faculty engagement in internationalization: international attitudes mediation - Yan, Liu Hai; Ping, Yang Su (Institute of Advanced Engineering and Science, 2025)
Globalization continues to reshape higher education, driving increased international exchanges and collaboration. This study investigates the impact of the international atmosphere on faculty engagement in internationalization (FEI), with a focus on local applied universities in China. Despite the recognized importance of faculty in facilitating internationalization efforts, limited research exists on their involvement. Utilizing surveys and structural equation modeling, data was collected from faculty members in local applied universities in China. The survey instrument covered demographics, perceptions of the international environment, engagement in international activities, and attitudes towards internationalization results indicate significant positive correlations between the international atmosphere, faculty international attitudes (FIA), and engagement in international activities. Specifically, the international atmosphere positively influences FIA and subsequent engagement in internationalization. Furthermore, FIA were found to partially mediate the relationship between the international atmosphere and engagement. This study contributes to the understanding of faculty involvement in internationalization efforts, addressing a gap in the literature. By identifying the factors influencing faculty engagement, institutions can develop targeted strategies to promote global engagement in higher education, ultimately enhancing the internationalization process.